From collusion to ruptura on Jordi Cuixart´s procedural strategy - Alonso de la Torre Merchán, Carlos (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
This paper analyzes Jordi Cuixart´s defense strategies during the special case 20907/2017 before spanish Supreme Court. The focus is made up from the work of Jacques Vergès and his distinction between rupture and collusion strategies, taking contributions from other sources that help to contextualize the analysis and understand the characterization of the justice as a political institution serving the established power, which is elementary to situate the work of Vergès and the behavior of Cuixart. It also has the aim of verifying the existence of political objectives that explain the defendant´s procedural behavior and the differencies that emerge between the instruction and the oral trial. Knowing those goals is useful to understand, on the one hand, the dichotomy between rupture and collusion over the basis of a current example; and on the other hand, the reasons that boost Cuixart, which helps to better understand the process and the scenarios that, after the trial, are appearing.